2017
DOI: 10.1038/s41598-017-05439-1
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale Metabolic Profiling identifies Novel Steroids linked to Rheumatoid Arthritis

Abstract: Recent metabolomics studies of Rheumatoid Arthritis (RA) reported few metabolites that were associated with the disease, either due to small cohort sizes or limited coverage of metabolic pathways. Our objective is to identify metabolites associated with RA and its cofounders using a new untargeted metabolomics platform. Moreover, to investigate the pathomechanism of RA by identifying correlations between RA-associated metabolites. 132 RA patients and 104 controls were analyzed for 927 metabolites. Metabolites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Previous studies of metabolomics are present for RA and ankylosing spondylitis (AS) . Table summarizes the major metabolite disturbances reported in these studies as compared to our findings.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies of metabolomics are present for RA and ankylosing spondylitis (AS) . Table summarizes the major metabolite disturbances reported in these studies as compared to our findings.…”
Section: Discussionmentioning
confidence: 53%
“…28,29 Steroid deficiency in RA patients has already been identified in several studies. [30][31][32] Other studies have shown a deficiency of both steroids, as well as other kinds of steroids, suggesting that RA is associated with the steroid pathway. 32,33 These steroids are known to be present in lower concentrations in patients who did not receive corticosteroid treatment compared to those who received treatment.…”
Section: Final Candidate Selectionmentioning
confidence: 99%
“…[30][31][32] Other studies have shown a deficiency of both steroids, as well as other kinds of steroids, suggesting that RA is associated with the steroid pathway. 32,33 These steroids are known to be present in lower concentrations in patients who did not receive corticosteroid treatment compared to those who received treatment. 32 We confirmed that the patient group recruited for our study did not receive corticosteroid treatment.…”
Section: Final Candidate Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we utilize two leading metabolomics platforms operated by Metabolon (M) and the Broad Institute (B), both with established track records of investigation in human biomarker research (14)(15)(16)(17)(18)(19). We hypothesized that analyses of a common set of samples obtained from patients with CKD on both nontargeted platforms would permit characterization of intraassay, day-to-day, and interassay variation as well as characterize the relationship between GFR and the metabolome.…”
Section: Introductionmentioning
confidence: 99%